Phenomenological Study in Revealing Village Fund Fraud - Riskiyadi, Moh. (APSSAI, 2025)
Research aims: This study aims to reveal the essence of village fund fraud committed against the village and its officials. Design/Methodology/Approach: This study uses an existential phenomenology approach to reveal the essence of village fund fraud in Nemor Village. Research findings: The study's results indicate that village fund fraud is seen from the village development planning meeting (Musrenbangdes) only ceremonial, the village secretary and treasurer are merely symbols, the BPD is controlled by the village head and community participation is tightly closed. The motivations behind village fund fraud are greed, opportunity, need, and disclosure. Theoretical contribution/Originality: This study examines village fund fraud differently. Revealing the essence underlying the occurrence of village fund fraud Practitioner/Policy implication: Factors causing village fund fraud must be signs for stakeholders to mitigate village fund fraud.